(3JdbjM aghe Cgd GdBKQ aj Yjhf GdJGQjN hGdSjQs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3GdMeO Ydi GMSGfg hCaVGdg gPG cJGH PcQJ ajg ef GdJhGQjN hGdSjQ afhfkG s
(3BNQgG (B:s
(3BNQ cJGH ? hGddg SHMGfg hJYGdi CbUi fgGjI GdMeO s
(3GfXQ Qbe (B188 (3JGQjNs
(3fSNI KGfjIs
(3fSNI NRGFfjI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs